Multiphysics Analysis of Contact Pressure Profile of Airless tires as compared to Conventional Tires - Ludvigsen, Søndre; Andleeb, Zahra; Khawaja, Hassan; Moatamedi, Mojtaba; Alzahabi, Basem (The International Journal of Multiphysics, 2020)
The harsh climate of the Arctic has always posed significant challenges to car drivers. The severe loss in traction due to snow and icing on the roads has led to an increased risk of collisions. The purpose of this work is to replace the conventional air-filled tire with a non-pneumatic tire to improve the grip in the Arctic conditions. The grip obtained for tires is determined by the weight of the car and the friction between the tire and the road. The friction coefficient, used to determine friction, is a function of the contact pressure. This research work involve obtaining a concentrated pressure profile for the airless tire, compared to a conventional tire. A finite element analysis using ANSYS® Workbench, is performed on two distinct models. The different pressure profiles of the models are analyzed, and the results proved the non-pneumatic tires have a more concentrated pressure profile with higher pressure values.